Time-varying parameters realized GARCH models for tracking attenuation bias in volatility dynamics. Issue 11 (1st November 2020) - Gerlach, Richard; Naimoli, Antonio; Storti, Giuseppe
Abstract : This paper proposes novel approaches to the modeling of attenuation bias effects in volatility forecasting. Our strategy relies on suitable generalizations of the Realized GARCH model by Hansen et al. [Realized garch: A joint model for returns and realized measures of volatility. J. Appl. Econom., 2012, 27(6), 877–906] where the impact of lagged realized measures on the current conditional variance is weighted according to the accuracy of the measure itself at that specific time point. This feature allows assigning more weight to lagged volatilities when they are more accurately measured. The ability of the proposed models to generate accurate forecasts of volatility and related tail risk measures, Value-at-Risk and Expected Shortfall, is assessed by means of an application to a set of major stock market indices. The results of the empirical analysis show that the proposed specifications are able to outperform standard Realized GARCH models in terms of out-of-sample forecast performance under both statistical and economic criteria.